Analysis of the prevalence and impact of burnout in university professors - Cunha , Maria Nascimento; Pinto , Sílvia Costa (Seven Editora, 2024)
In order to explore the prevalence and factors associated with burnout in university professors and for a detailed assessment of the main and secondary symptoms of burnout, including exhaustion, mental distance, inability to control cognitive and emotional, psychological distress and psychosomatic complaints, we chose to use the BAT - Burnout Assessment Tool. The results indicate a significant prevalence of burnout among teachers, with emotional exhaustion being the most affected dimension, also highlighting the influence of factors such as workload and intense emotional demands. The findings underline the need for institutional interventions and management policies to mitigate burnout and promote well-being in the academic environment. This work contributes to the understanding of burnout in higher educational contexts, suggesting future directions for institutional research and practice. DOI:https://doi.org/10.56238/sevened2024.016-013